Reply to “Improving Brain-Gut Studies in Crohn’s Disease: Methodological Considerations” - Thomann, Anne K.; Wolf, Robert Christian (Inflammatory bowel diseases, 2025)
We greatly appreciate the authors’ comments regarding our previous article and agree that more research is urgently needed to increase our understanding of brain-gut interactions in Inflammatory Bowel Diseases (IBD).The approach chosen in our study examined unprovoked brain activity with the aim to find general differences between different disease states of Crohn’s Disease and associations that might help to explain neuropsychiatric symptoms. However, we fully agree that resting-state functional magnetic resonance imaging (rs-fMRI) can only capture certain aspects of brain activity, specifically those occurring at rest, rather than under experimental conditions with external task demands. While task-based paradigms can undoubtedly provide a more dynamic and functional representation of neural capacities and disturbances, there is no general consensus on the optimal tasks for addressing specific research questions. Yet, future research could start by implementing tasks commonly used in depression or anxiety research,1 preferably in longitudinal settings as suggested by the authors. Also, the combination of rs- and task-based fMRI seems promising in order to detect shared network dysfunctions.